Community Perception and Digital Accountability in Village Governance: The Case of JALANTOL Application in Jatirenggo Village - Annisa Miftahul Janna Annisa Miftahul Jannaa; Suljatmiko Suljatmiko; Dedi Susanto Dedi Susanto (JOURNAL OF GOVERNMENT SCIENCE, 2025)
This study analyzes public perception and digital accountability in the implementation of the JALANTOL application as a village e-governance innovation. Using a mixed method of sequential explanatory with 95 respondents and non-participatory observation, this study integrates the Technology Acceptance Model (TAM) and the UTAUT framework to measure affective, cognitive, and conative responses. The results showed good perceptions of the application's digital accountability, perceived usefulness (mean = 3.02), ease of use (mean = 2.78), and service relevance (mean = 3.05). Younger respondents showed stronger acceptance, while older groups faced usability barriers. This study also found that JALANTOL's real-time complaint feature enables participatory digital accountability by encouraging transparency and traceable public monitoring. These findings suggest that effective village e-services are not only based on a sophisticated set of technologies, but also community alignment, inclusive design, and trust-based participation. This study contributes to the understanding of micro-level e-government adoption and highlights the need to embed digital accountability in the user experience.